Thibbun Nabawi dalam Perspektif Yusuf Al Qaradhawi - Nur Adhi, Hanif Acep (The Hadith Department, Faculty of Ushuluddin and Islamic Thought, State Islamic University of Raden Fatah Palembang., 2023)
Abstract This study aims to explore the views of Sheikh Yusuf Al Qaradawi on Thibbun Nabawy (Prophet Medicine). One of the recent Muslim trends is the revival of thibbun nabawy. And one of the other sides, is denying modern medicine that comes from the west. This extreme attitude has given rise to many difficulties among Muslims in terms of the health and safety of the human soul. This research method uses library research . This research aims to determine whether Thibbun Nabawi is a human scientific experiment or is he part of a divine revelation. Sheikh Yusuf Al Qaradawy as a contemporary scholar has an interesting perspective on this theme. The results of the study show that the hadiths about the thibbun nabawi are not placed as tasyri as the arguments about prayer, fasting and zakat. So that treatment can be adapted to the times, and that includes the spirit of thibbun nabawi. The contribution of this research is that Muslims are not worried about using modern medical treatment, because this assumption is different from thibbun nabawi. Keywords: thibbun nabawi, modern medicine, Yusuf Al Qaradawi. Abstraksi Penelitian ini bertujuan untuk menggali pandangan Syekh Yusuf Al Qaradhawi tentang Thibbun Nabawy(Kedokteran Nabi). Salah satu tren umat Islam akhir-akhir ini adalah kebangkitan kembali thibbun nabawy. Dan salah satu sisi lainnya, adalah mengingkari pengobatan modern yang berasal dari Barat. Sikap ekstrem tersebut telah melahirkan banyak kesulitan di tengah umat Islam dari sisi kesehatan dan keselamatan jiwa manusia. Metode penelitian ini menggunakan studi kepustakaan. Penelitian ini bertujuan menempatkan thibbun nabawi, apakah dia sebagai percobaan ilmiah manusia ataukah ia bagian dari wahyu ilahi. Syekh Yusuf Al Qaradhawy sebagai ulama kontemporer memiliki perspektif menarik terkait tema ini. Hasil dari penelitian menunjukkan bahwa hadits-hadits tentang thibbun nabawi tidak ditempatkan sebagai tasyri sebagaimana dalil-dalil tentang sholat, puasa dan zakat. Sehingga pengobatan bisa disesuaikan dengan perkembangan zaman, dan itu termasuk ruh dari thibbun nabawi. Kontribusi dari penelitian ini adalah umat Islam tidak waswas menggunakan pengobatan medis modern, karena anggapan itu menyelisihi thibbun nabawi. Kata kunci : thibbun nabawi, kedokteran modern, Yusuf Al Qaradhawi.